Utilizing of the metallurgical slag for production of cementless concrete mixtures - D. Baricová; A. Pribulová; P. Demeter; B. Buľko; A. Rosova (Metalurgija, 2012)
In process of pig iron, steel and cast iron production besides main product, also secondary products are formed, that have character of secondary raw materials and industrial wastes. The most abundant secondary product originating in the metallurgical process is furnace slag. Total amount of accured slag, also its chemical, mineralogical, physical – chemical properties and similarity with natural stones predestinate its utilisation in different fields of industry. The contribution deals with production of cementless concrete mixtures, where the main parts were formed by blast furnace granulated slag grinded and different gravel slag from blast furnace, oxygen converter and electric arc furnace. As activators of solidification different kinds of water glass were tested.